Isomerisation of 1,4-dichlorobenzene using highly acidic alkali chloroaluminate melts. - Meßner, Julia; Schulz, Peter; Taccardi, Nicola; Kuhlmann, Sven; Wasserscheid, Peter (Chemical Communications, 2014)
The isomerization reaction of 1,4-dichlorobenzene leading to the thermodynamically favored and tech. desired 1,3-dichlorobenzene has been studied comparing highly acidic chloroaluminate melts with org. imidazolium and alkali metal ions. Interestingly, the inorg. melts show much higher reactivity and full recyclability if small AlCl3 losses are compensated and the reaction is carried out under slight HCl pressure. [on SciFinder(R)]
Keywords: dichlorobenzene isomerization acidic alkali chloroaluminate melt

Method for the isomerization of substituted aromatic substances using a molten metal salt. - Kuhlmann, Sven; Weber, Hans-Martin; Böger, Uwe; Wasserscheid, Peter; Schlenk, Stefan; Meßner, Julia (2013)
A method for the isomerization of substituted arom. substances such as, an example, p-dichlorobenzene comprises isomerization at 100 - 220° in the presence of a mixt. of molten salts comprising AlCl3, AlBr3 and GaCl3 with chlorides of Li, K, Naor Cs at ratios (1:1) - (10:1). Thus, mixing in a glass autoclave at 170° 20 mol.% AlCl3 with 10 mol.% LiCl, adding 250 g p-dichlorobenzene, stirring 4 h at 170° gave a mixt. contg. 53% m-dichlorobenzene, 44% p-dichlorobenzene and 3% o-dichlorobenzene. [on SciFinder(R)]
Keywords: isomerization substituted arom substance molten metal salt

Thermodynamic Analysis of lsomerization Equilibria of Chlorotoluenes and Dichlorobenzenes in a Biphasic Reaction Systems Containing Highly Acidic Chloroaluminate Melts - Verevkin, Sergey P.; Meßner, Julia; Emel'Yanenko, Vladimir N.; Gantman, Mikhail; Schulz, Peter; Wasserscheid, Peter (Journal of Physical Chemistry B, 2016)
Thermodynamics and kinetics of the isomerization of chlorotoluenes and dichlorobenzene to the technically desired meta-isomers have been studied in the presence of highly acidic chloroaluminate melts with alkali metal and organic imidazolium cations. Enthalpies of four isomerization processes in reacting systems of chlorotoluenes and dichlorobenzene were obtained from temperature dependencies of the corresponding equilibrium constants in the liquid phase. Experimental reaction enthalpies, enthalpies of vaporization, and absolute vapor pressures of chlorotoluenes and dichlorobenzene have been used for the validation of quantum-chemical methods to predict thermodynamic functions of the four reactions under study successfully. Values of the standard Gibbs energies of formation, standard enthalpies and entropies of formation of chlorotoluenes and dichlorobenzenes in the liquid and in the gas phase have been derived. These values allow optimization of liquidliquid biphasic manufacturing technologies for halogen-substituted benzenes.